Cinematographic anatomy of the Ecuadorian documentary. Detailed study of the visual, sound and syntactic codes of the documentary Con mi corazón en Yambo (2011) - Noboa Cevallos, Juana Cecibel (Nawi, 2024)
This research focuses on the detailed analysis of Con mi corazón en Yambo (2011), an emblematic documentary of Ecuadorian cinema, with the purpose of understanding how visual, sound, graphic, syntactic and political cinematographic codes intertwine to transmit meanings. and build narratives. An exhaustive analysis of selected sequences from the documentary was carried out, allowing a classification of the montage according to its type and modality. The approaches of Francesco Casetti and Federico Di Chio, as well as Sergei Eisenstein, together with a comparative analysis based on an interview with the filmmaker who produced the documentary, allowed us to completely unravel its structure. This approach not only explores the influence of these elements on cultural representation, aesthetics and communication in Ecuadorian documentary film, but also reveals the artistic richness, cultural message and narrative uniqueness of this film. Thus, a deeper and more detailed understanding of documentary cinema in Ecuador is offered.
Keywords: Ecuador; cinema; documentary; cinematographic codes; montage